THE ROLE OF HISTORICAL TOURISM IN PROMOTING NATIONAL IDENTITY AND HERITAGE (International Journal of Food and Nutritional Sciences, 2022)
The aim of this research paper lies in studying the role of historical tourism in creating national identity and promotion of cultural heritage. Through the opportunity for direct engagement with landmark sites, artefacts and narratives of importance, historical tourism acts as a highly effective medium through which the wider public can learn about the rich tapestry of a nation's past. This study investigates the manner in which historical tourism would not only serve as a source of economic development of areas, but also increases and enhances citizens’ collective identity and pride. This paper discusses the interaction between conservation of heritage and tourism through the analysis of case studies at various countries where several historical sites are maintained, the challenges faced, and the strategies adopted to maintain a balance between tourism and preservation. The potential of historical tourism as a tool for cultural education, the national unity, and the protection of historical legacies in the future also ensue from the findings.